2019
DOI: 10.1002/csr.1838
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the business case for corporate social responsibility and firm performance

Abstract: The outcome of existing studies on the influence of corporate social responsibility (CSR) initiatives on firm performance remains inconclusive though several studies to amplify the impact of CSR activities are well documented. We conducted an extensive review to detect if there are conceivable methodological errors, societal performance, and corporate performance. The analysis reveals a clearer understanding of the relationship between business performance and CSR effect. Our results attest to the inconclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 128 publications
(142 reference statements)
1
83
1
6
Order By: Relevance
“…Fourth, this research contributes to the studies on the significant effect of regional characteristics on corporate policy. According to Wu, Lin, and Liu (2016), religiosity, which is a local cultural characteristic, significantly influence corporate social responsibility activities by imposing “more demand for corporate social responsibility” and condemning “corporate activities that will create social concerns.” Therefore, this study casts additional light on the impact of religiosity and religious affiliation on ESG disclosure (Kong, Antwi‐Adjei, & Bawuah, 2020; Martínez‐Ferrero, Ruiz‐Cano, & García‐Sánchez, 2016). The rest of the paper is organized as follows: Section 2 presents the theoretical analysis and develops the hypotheses; Section 3 presents the sample and the regression model; Section 4 discusses the empirical results; and Section 5 concludes the study.…”
Section: Introductionmentioning
confidence: 87%
“…Fourth, this research contributes to the studies on the significant effect of regional characteristics on corporate policy. According to Wu, Lin, and Liu (2016), religiosity, which is a local cultural characteristic, significantly influence corporate social responsibility activities by imposing “more demand for corporate social responsibility” and condemning “corporate activities that will create social concerns.” Therefore, this study casts additional light on the impact of religiosity and religious affiliation on ESG disclosure (Kong, Antwi‐Adjei, & Bawuah, 2020; Martínez‐Ferrero, Ruiz‐Cano, & García‐Sánchez, 2016). The rest of the paper is organized as follows: Section 2 presents the theoretical analysis and develops the hypotheses; Section 3 presents the sample and the regression model; Section 4 discusses the empirical results; and Section 5 concludes the study.…”
Section: Introductionmentioning
confidence: 87%
“…The rationale behind CSR is that in addition to the commercial activities, the commercial companies must give proper concern for the society wellbeing, which integrally extends to a healthy living environment (McWilliams & Siegel, 2001). Despite the positive effect of CSR on the companies' financial outputs being long-debated (Cochran & Wood, 1984;Kong et al, 2020;Lee & Park, 2009;Paton & Siegel, 2005;Moneva et al, 2020), CSR is believed to bring the non-monetary benefits to the companies, such as improving the brand image, brand awareness, and brand differentiation strategy (Diehl et al, 2016;Griffin & Mahon, 1997;Miller et al, 2020;P erez & del Bosque, 2015). When a company has well-planned socially-responsible initiatives, the individuals tend to develop a positive impression about the company (Sen & Bhattacharya, 2001).…”
Section: Corporate Social Responsibility In Tourismmentioning
confidence: 99%
“…A substantial number of scholarly studies have been conducted into the impact of CSR on OP. However, the results to date have been conflicting (Kong, Antwi‐Adjei, & Bawuah, ). For example, some studies found a positive and significant impact (Borger & Kruglianskas, ; Chih, Miao, & Chuang, ), while a number of other authors report a negative association between CSR and OP (Becchetti, Ciciretti, Hasan, & Kobeissi, ).…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%